Architectures of deviation: exploring the spatial protocols of contemporary videogames. Issue 3 (24th March 2016) - Pearson, Luke
Abstract : This essay attempts to outline the ways in which contemporary videogames produce spatial experiences, and how architects might interrogate their unique media form. Framing videogames as both computational constructions and cultural artefacts, the paper places the study in a lineage of architectural thinkers examining 'pop-culture' and technology. This draws from the Smithson's writings on advertisements as technical images, Venturi Scott-Brown's studies on symbolism, through to Reyner Banham's definition of mass produced gizmos . The paper first outlines the importance of videogames on society and their Smithsonian impulses towards architectural design. To support this, I examine the work of game theorists such as Espen Aarseth and Ian Bogost. Aarseth argues that game spaces sever certain ties and 'deviate' from reality in order to become playable spaces. Bogost contends that game rules produce 'procedural rhetoric' - games may advance arguments through the playing of their rules. Reading from these theories I argue that these rule-based breaks from the real are a potent site for architectural speculation. The second section comprises design case studies scrutinising existing game worlds and producing new videogames as architectural experiments. I begin by examining the significance of symbolism in videogame worlds, and how this might provide alternative trajectories for digital architectural design. I subsequently explore Atkinson and Willis' concept of the ludodrome, slippages between virtual and real, and discuss Ubiquity, a game I produced to explore this condition. I return to Banham's Great Gizmo, alongside PW Singer's writings on military robotics, to see the gamepad as a new order of gizmo for colonising space. And I discuss 'Grand Theft Auto V''s loading screen as a manifestation of satellite imagery aesthetics that collapse space. The paper concludes that games are powerful media for spatial experimentation and we must prepare for new generations of designers highly influenced by such 'deviated' architectures.